Sector-Based Action Against Corruption A Guide for Organisations and Professionals - Pyman, Mark.; Heywood, Paul M.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book provides an accessible insight into how to tackle corruption in organisations and institutions. It explains how to recognise and analyse corruption issues, together with knowledge and advice on how they can be avoided, prevented, or minimised. It also provides a framework through which readers can examine what strategies are available to tackle corruption issues, a rationale for how to prioritise strategies depending on circumstances and context, and guidance on how to critique various options. The book will appeal to professionals and practitioners, as well as academics interested in governance and corruption. Mark Pyman is co-founder of the online network CurbingCorruption.com, having previously created and led Transparency International$1 (Bs global programme tackling defence and security corruption. He served as a Commissioner in Afghanistan$1 (Bs Anti-Corruption Committee (MEC). Paul M. Heywood holds the Sir Francis Hill Chair of European Politics at the University of Nottingham, UK. His research focuses on political corruption, institutional design, and state capacity. With Mark, he is also co-founder of the online network CurbingCorruption.com.s
Introduction: 1. Corruption Basics -- 2. Corruption as a Management Issue. Part I: Analysis: 3. Sector -- 4. Focus -- Part II: Remediation Approach: 5. Broad Framing -- 6. Specific Measures -- 7. Choosing Options -- 8. Last words.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Political science; Public administration; School management and organization; School administration; International organization; Governance and Government; Public Management; Organization and Leadership; International Organization